The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/03637750701716578
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in the Persuasiveness of Evidence Types and Evidence Quality

Abstract: Cultural differences in reasoning and persuasion have mainly been documented for the East*West divide. Nisbett (2003) expects such differences to be absent for Western cultures because of their shared Grecian inheritance. The results of two experiments, however, show that France and The Netherlands, both Western European countries, differ with respect to the persuasiveness of different evidence types. In Study 1 (N0600), cultural differences occurred between the relative persuasiveness of anecdotal, statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
3
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 23 publications
3
59
3
14
Order By: Relevance
“…This explanation found no support, as the scores on Need for Cognition (NFC) for French (M = 3.28, SD = 0.75) and Dutch (M = 3.13, SD = 0.75) participants did not significantly differ (t (216) = 0.02, p = .99). A cultural difference was found, though, on the preference for expert information: contrary to earlier findings (Hornikx and Hoeken 2007), the Dutch (M = 2.66, SD = 0.76) had a higher preference for expert information than the French (M = 2.40, SD = 0.87; t (216) = 2.69, p < .01). Preference for expert information was therefore not considered an alternative explanation for the cross-cultural difference in expertise judgments.…”
Section: Hypothesiscontrasting
confidence: 54%
See 3 more Smart Citations
“…This explanation found no support, as the scores on Need for Cognition (NFC) for French (M = 3.28, SD = 0.75) and Dutch (M = 3.13, SD = 0.75) participants did not significantly differ (t (216) = 0.02, p = .99). A cultural difference was found, though, on the preference for expert information: contrary to earlier findings (Hornikx and Hoeken 2007), the Dutch (M = 2.66, SD = 0.76) had a higher preference for expert information than the French (M = 2.40, SD = 0.87; t (216) = 2.69, p < .01). Preference for expert information was therefore not considered an alternative explanation for the cross-cultural difference in expertise judgments.…”
Section: Hypothesiscontrasting
confidence: 54%
“…When claims are highly improbable (e.g., "smoking reduces the risk of lung cancer"), people disbelieve such claims regardless of the support provided (see Edwards and Smith 1996). Eight claims were borrowed from Hornikx and Hoeken (2007). A pretest had shown these eight claims to be moderately probable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental studies, we found substantial support for this hypothesis: violation of the criteria trustworthiness (Hoeken et al 2012(Hoeken et al , 2014 and recency (Hoeken et al 2012) for argumentation from authority, relevant similarities and irrelevant dissimilarities for argumentation from analogy (Hoeken and Hustinx 2009;Hoeken et al 2012), number of examples (Hoeken and Hustinx 2009;Hoeken et al 2014;Hornikx and Hoeken 2007) and relevance of example for argumentation from example (Hoeken et al 2014), cause sufficiency and cause relevance for argumentation from cause to effect (Hoeken et al 2014) and desirability of effect (Hoeken et al 2012) for argumentation from consequence resulted in a significantly lower claim acceptability. Only violation of the criteria expertise (for argumentation from authority) and effectivity (for argumentation from consequence) did not always reveal the effect predicted (Hoeken et al 2012(Hoeken et al , 2014, possibly as a result of too subtle manipulations.…”
mentioning
confidence: 69%